SOME OF THE MECHANISMS OF EXTRACORPOREAL PHOTOCHEMOTHERAPY IN SOLID ORGAN TRANSPLANTATION - A. V. Vatazin; A. B. Zul'karnaev; A. V. Kil'djushevskij; V. A. Fedulkina; M. Krstic (Вестник трансплантологии и искусственных органов, 2014)
Reducing the risk of kidney transplant rejection is a perspective trend in modern medical science. One of the promising methods for reducing the activity of immune conflict between the recipient and the donor organ and the achievement of partial immunological tolerance is photochemotherapy. This method is widely used in over- seas heart and lung Transplantation. Domestic experience of applying this method in renal transplant recipients is extremely small. In this review of literature a modern representation of the scientists on the mechanism of action of this method is presented.